Effects of Exogenous Recombinant APC in Mouse Models of Ischemia Reperfusion Injury and of Atherosclerosis - Wildhagen, Karin C. A. A. (Public Library of Science, 2014)
Activated protein C (APC) is a serine protease that has both anticoagulant and cytoprotective properties. The cytoprotective effects are protease activated receptor 1 (PAR-1) and endothelial protein C receptor (EPCR) dependent and likely underlie protective effects of APC in animal models of sepsis, myocardial infarction and ischemic stroke. S360A-(A)PC, a variant (A)PC that has no catalytic activity, binds EPCR and shifts pro-inflammatory signaling of the thrombin-PAR-1 complex to anti-inflammatory signaling. In this study we investigated effects of human (h)wt-PC, hS360A-PC, hwt-APC and hS360A-APC in acute (mouse model of acute myocardial ischemia/reperfusion (I/R) injury) and chronic inflammation (apoE(−/−) mouse model of atherosclerosis). All h(A)PC variants significantly reduced myocardial infarct area (p<0.05) following I/R injury. IL-6 levels in heart homogenates did not differ significantly between sham, placebo and treatment groups in I/R injury. None of the h(A)PC variants decreased number and size of atherosclerotic plaques in apoE(−/−) mice. Only hS360A-APC slightly affected phenotype of plaques. IL-6 levels in plasma were significantly (p<0.001) decreased in hwt-APC and hS360A-PC treated mice. In the last group levels of monocyte chemotactic protein 1 (MCP-1) were significantly increased (p<0.05). In this study we show that both hwt and hS360A-(A)PC protect against acute myocardial I/R injury, which implies that protection from I/R injury is independent of the proteolytic activity of APC. However, in the chronic atherosclerosis model hwt and hS360-(A)PC had only minor effects. When the dose, species and mode of (A)PC administration will be adjusted, we believe that (A)PC will have potential to influence development of chronic inflammation as occurring during atherosclerosis as well.